STRATEGY TO ENHANCE INDONESIA'S LEADING INDUSTRIAL CENTERS COMPETITIVENESS - Anggraeni, Rila; Ayuni, Risca Fitri; I., M. Abdi Dzil (Universitas Brawijaya, Indonesia, 2020)
The industrial centerhas a significant role in supporting the national economy through its ability to absorb labor, technology transfer, and add value to products. The strength of industrial centers is its resilience in facing unstable economic conditions. Government through Nawa Cita has included industrial elements as part of the priority agenda to improve welfare through independence in the economic field. Malang is the second-largest city in East Java which has numerous industrial centers as an economic basis. The industrial centers in Malang City to be mentioned are the Sanan tempe chips, the Blimbing furniture industry, the Arjosari rattan industry, and the Dinoyo ceramics industry. The centers of the industry need to develop so that they can compete with products from other regions and countries. This study aims to map existing industrial centers in Malang and determine the best industrial centers or leading industrial centers by using 12 criteria of regionally superior products according to Minister of Home Affairs Regulation of Indonesia Republic Number 9 of 2014 concerning Guidelines for Regional Superior Product Development. Furthermore, this study will analyze the weaknesses, strengths, opportunities, and threats of the leading industrial centers. Then the results of the analysis are mapped into a matrix of internal and external factors as a basis for determining strategies to improve the competitiveness of leading industrial centers. The research used the Analytical Hierarchy Process (AHP) and SWOT Analysis as the research method. The information explored through Focus Group Discussion (FGD) and in-depth interviews. The results showed that Malang City has 4 (four) leading industrial centers, namely tempe chips, ceramics, furniture, and rattan. On the IE matrix, the position of Malang's leading industrial centers is in cell V which is maintaining and defending. In this cell, the strategy that must be carried out by the superior industrial centers of Malang City is an intensive strategyby conducting market development and product development. The market development strategy is to introduce existing products or services to a geographical area or a new market segment. Based on the QSPM matrix, the alternative strategy that has the highest TAS score is to increase demand by using social media and supporting clusters (tourism destination) as a marketing channel supported by the superiority of the products and services offered.